(untitled) (Neo Scientific Peer Reviewed Journal, 2024)
Symbolic meanings of colors related to the differences in the mentality of each nation, i.e. life traditions, customs, and beliefs. In linguistics, colors show that they have semantic differences beyond their color sign, they have ethnographic, symbolic meanings and meanings related to tradition. The article focuses on revealing the usage differences and different meanings of the colors in clothing terms.